THE PREVALENCE OF OVERWEIGHT AND OBESITY AMONG CHILDREN IN MIDDLE SCHOOL WITHIN THE BIHOR - HAJDÚ-BIHAR EUROREGION - Norbert Csaba LUKÁCS; Iacob HANȚIU (Cluj University Press, 2016)
Introduction. The early stage of adolescence, between the age of 11 and 14, is accompanied by a great fluctuation of the values of sudden physical growth, of temperament and of personality. Periodical monitoring of somatic indicators and determining the body mass index (BMI) are methods necessary for monitoring the state of health of schoolchildren. Goals. The goal of this study is to assess the prevalence of overweight and obesity among children in middle school within the Bihor-Hajdú-Bihar Euroregion and to compare the obtained results with the results of other studies of this nature. Subjects and methods. The sample group was made up of 934 middle school students from the Bihor-Hajdú-Bihar Euroregion. The method used was anthropometry. The body mass index was calculated in accordance with the BMI reference chart according to age and gender. The results of the measurements were statistically processed with the SPSS program. The descriptive analysis was performed and the differences between the average values were tested with the independent samples t-test. Results. The results of the study have shown increased values of height and weight for both genders, from one grade to the other; for girls higher mean values than for boys. 15.31% of the total number of subjects were overweight and 11.99% were obese, resulting a total percentage of 27.30% of individuals with excess weight. The independent samples t-test: t (933) = -.443, p=0.658, shows that statistically speaking there are no significant differences between the mean BMI values of the subjects from Bihor (M=20.42, SD=4.10, n=474) and the mean BMI values of the subjects from Hajdú-Bihar (M=20.54, SD=4.16, n=460). Conclusions. The prevalence of overweight and obesity in Bihor decreases with age, from 35.5% in 5th grade to 19.5% in 7th grade, after which again it tends to increase. In Hajdú-Bihar this decrease is uninterrupted from 34% in 5th grade to 19% in 8th grade. Incidența supraponderalității și obezității la copiii din ciclul gimnazial din euroregiunea Bihor-Hajdú-Bihar. Introducere. Parcurgerea adolescenței timpurii, cu limite între 11 și 14 ani se produce cu o mare variabilitate a indicilor creșterii fizice bruște, ai temperamentului și ai personalității. Supravegherea periodică a indicatorilor somatici și determinarea valorii indicelui de masă corporală (IMC) reprezintă metode necesare de monitorizare a stării de sănătate a școlarilor. Obiective. Obiectivul acestui studiu a fost să evaluăm incidența supraponderalității și obezității la copiii gimnaziali din Euroregiunea Bihor, Hajdú-Bihar și să comparăm rezultatele obținute cu cele din alte studii asemănătoare. Subiecți și metode. Eșantionul a fost format din 934 de elevi din ciclul gimnazial din euroregiunea Bihor-Hajdú-Bihar. Metoda de lucru a fost antropometria. Indicele de masă corporală s-a calculat conform hărții de referință a IMC după vârstă și gen. Datele măsurătorilor au fost prelucrate statistic cu ajutorul programului SPSS. A fost făcută analiza descriptivă iar diferențele dintre medii au fost testate cu ajutorul testului t pentru eșantioane independente. Rezultate. Rezultatele studiului au evidențiat valori crescute, de la o clasă la alta, ale taliei și greutății la ambele genuri; valori medii superioare la fete, comparativ cu băieții. Din totalul populației 15.31% din subiecți au fost supraponderali și 11.99% obezi, rezultând o pondere de 27.30% a celor cu excedent de greutate. Testul t pentru eșantioane independente: t (933) = -.443, p= .658, arată că din punct de vedere statistic nu sunt diferențe semnificative între mediile IMC subiecților din Bihor (M=20.42, SD=4.10, n=474) și ale celor din Hajdú-Bihar (M=20.54, SD=4.16, n=460). Concluzii. Prevalența supraponderalității și obezității în Bihor scade cu vârsta, de la 35% în clasa a V-a la 19% în clasa a VII-a, după care apare din nou o tendință de creștere. În Hajdú-Bihar această descreștere este neîntreruptă de la 33% în clasa a V-a la 19% în clasa a VIII-a.  Keywords: supraponderalitate, obezitate, preadolescență, talie, greutate